DESIGN SYSTEM FOR PRACTICE EXAM QUESTION BAN USING MACROMEDEIA DREAMWEAVER 8.0 IN HANG TUAH 1 JAKARTA HIGH SCHOOL - Artha Wulan Dhika; Yudi Irawan Chandra (Jurnal Sistem Informasi, 2010)
School exams is one the implementation of curriculum that can not be separatedfrom one other activities are conducted on each end of the school year attendedall by students attending school in other to complete one level of education toenter higher education. Exam practice online or also known as Question Bankwhich contains a collection of matter in it about the lesson. Practice ExamQuestion Bank is one of the instructional media effectively and efficiently,students can receive lessons in indefinitely because of Systems Practice ExamQuestion Bank can be accessed at any time. Therefore, the authors propose tomake the Design System Practice Exam Question Bank thst can help students inan exam help to measure the ability of the students Hang Tuah 1 Jakarta HighSchool in capturing lessons